Can Biomedicine be Considered as an Alternative Healing? Engaging with the Ideas of Gregory Maskarinec - Dahal, Kapil Babu (Dhaulagiri Journal of Sociology and Anthropology, 2023)
In constant interactions with the select contributions of late Gregory Masakarinec, this paper analyzes the practices of shamanism as he had portrayed, mainly through his writings. While engaging with his ideas and portrayal, I will relentlessly engage with other relevant literature from different genre of medical anthropology which have dealt with health, illness and healing practices. Questioning the hegemonic presence of biomedicine in the field of health care, this article shows that even biomedicine can be considered as an alternative healing practice in typical social and cultural context of healing.